Odpowiedzi

2010-04-07T19:14:50+02:00
A)1*(-3x+2y-7)=-3x+2y-7
b)-1*(5k-7l+m)=-5k+7l-m
c)(2-14t+3p)*(-1)=-2+14t-3p
d)(5x-6y-3)/1=5x-6y-3
e)(-¾p+4w-pw)/(-1)=¾p-4w+pw
f)(2x-⅙y+4)/(-½)= -4x+⅓y-8
2010-04-07T19:17:48+02:00
1*(-3x+2y-7)=-3x+2y-7
b)-1*(5k-7l+m)=-5k+7l-m
c)(2-14t+3p)*(-1)=-2+14t-3p
d)(5x-6y-3)/1=5x-6y-3
e)¾p+4w-pw)/(-1)=-¾p-4w+pw
F)(2x-⅙y+4)/-½=-4+⅓y-8
2010-04-07T19:17:55+02:00
A)1*(-3x+2y-7)= -3x+2y-7
b)-1*(5k-7l+m)= -5k+7l-m
c)(2-14t+3p)*(-1)= -2+14t-3p
d)(5x-6y-3)/1= 5x-6y-3
e)(-¾p+4w-pw)/(-1)=¾p-4w+pw
f)(2x-⅙y+4)/(-½)= -1x+(sorki ale mój komputer nie widzi tego znaku ale musisz to na 2 podzielić)y-2